Determinação de 'SB' e 'PB' em embalagens de poli(tereftalato) de etileno (PET) por espectrometria de absorção atômica com fonte contínua e de alta resolução em forno de grafite empregando amostragem direta de sólidos - Silva, Tiago Varão [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Methods development were proposed for the determination of Sb and Pb in polyethylene terephthalate (PET) package by high-resolution continuum source atomic absorption spectrometry using direct solid sampling approach. Direct analysis using aqueous standards calibration was possible by using a proper heating program of atomizer and 5 μg Pd and 2.5 μg Mg as modifier in presence of 0.05% (m/v) Triton X-100. With regards to Sb, the pyrolysis and atomization temperatures were 1600°C and 2200°C, respectively. Calibration curves in the 0 – 100 ng range with linear correlation coefficient better than 0.9997 were obtained. The characteristic mass and limit of detection (LOD) were 1.0 ng Sb and 0.6 ng Sb, respectively. The relative standard deviation was 2.8%. For Pb, the of pyrolysis and atomization temperatures were 1400°C and 2000°C, respectively. Calibration in the 0 - 160 pg working range was obtained (R=0.9998) and the relative standard deviations were  4%. The characteristic mass was 5.2 pg Pb and the LOD was 4.9 pg Pb. Studies on homogeneity and minimal mass showed that acceptable precision and accuracy for Sb and Pb may be acquired if masses in the 0.3 - 0.4 mg and 0.5 - 0.8 mg were respectively weighted. PET samples at different colors were analyzed by the proposed method based on direct soid sampling. The concentrations varied from 176.7 to 250.1 mg kg-1 Sb and 26.5 to 80.9 pg mg-1 Pb. These results were in agrement with those obtained by high-resolution continuum source flame atomic absorption spectrometry (for Sb) and inductively coupled plasma mass spectrometry (for Pb) at 95% confidence level (except for the colorless PET).

Foram desenvolvidos métodos de determinação de Sb e Pb por espectrometria de absorção atômica com fonte contínua e alta resolução empregando amostragem direta de sólidos. A determinação direta de Sb e Pb foi possível com calibração em meio aquoso utilizando 5 μg de Pd e 2,5 μg de Mg em presença de 0,05% (m/v) de Triton-X como modificador químico. Para o Sb, as temperaturas de pirólise e de atomização foram 1600 °C e 2200 °C respectivamente. O método apresentou massa característica de 1,0 ng e limite de detecção de 0,6 ng. Para o Pb, as temperaturas de pirólise e de atomização foram 1400 °C e 2000 °C respectivamente. A massa característica foi de 5,2 pg e o limite de detecção 4,9 pg. Os desvios padrões relativos do Sb e Pb foram de 2,8% e 4% respectivamente. Estudos de homogeneidade e massa mínima sugeriram boa precisão e exatidão dos métodos na determinação de Sb e Pb em embalagens PET, quando massas entre 0,3 e 0,4 mg para Sb e 0,5 a 0,8 mg para Pb foram utilizadas. Quatro amostras de embalagens PET de diferentes cores foram analisadas pelo método proposto, as concentrações variaram 176,7 a 250,1 mg kg-1 para Sb e de 26,5 a 81,7 pg mg-1 para Pb. Os resultados comparativos obtidos para Sb e Pb empregando HR-CS FAAS e ICP–MS respectivamente, foram concordantes ao nível de 95% de confiança, exceto para o Sb na amostra de PET incolor. O método mostrou-se viável para quantificação dos analitos propostos podendo ser utilizado para controle de qualidade dos PETs, especialmente os que armazenam produtos alimentares.
Keywords: Quimica analitica; Antimonio; Chumbo; Embalagens; Contaminação; Antimony